Macro-Appraisal and Duplication of Information: Federal Real Property Management Records - Piché, Jean-Stéphen (Archivaria, 1995)
This article explores a methodology to deal with front-end appraisal and backlog reduction of large volumes of similar records held by different creating institutions. The first section also briefly explores some recent developments in the theory and methodology of macro-appraisal, specifically the relationship between analyses that are focused on function and those that are focused on structure and their relative merits on the targeting of archival priorities. Such targeting among many groups, series, systems, and creators of records must occur before individual series, files, or items are actually appraised. The bulk of the article demonstrates how an analysis of a pan-institutional function that generates like records can help archivists better determine the (relative) archival value of such records. The case in point is the Government of Canada real property management records. RÉSUMÉ Cet article propose un méthodologie d’évaluation archivistique de documents similaires créés par des institutions différentes et qui documentent une activité commune. Un survol des méthodes et théories de macro-évaluation archivistique, lesquelles reposent sur l’analyse des fonctions et des structures institutionnelles servant à identifier les priorités d’acquisition, constitue la première partie de cet article. Une telle analyse des différents groupes, séries, systèmes et créateurs de documents doit précéder l’évaluation des documents. L’argumentation centrale de cet article vise à démontrer comment une analyse d’une fonction pan-gouvernementale générant des documents similaires peut aider les archivistes à déterminer la valeur archivistique de ces documents. La présente étude porte sur les documents créés par la gestion des biens immobiliers du gouvernement fédéral canadien.